DESIGN OF POTENTIAL CELLULASE PRIMER USING MULTIPLE SEQUENCE ALIGNMENT METHOD - Bahrul Ulum; Wisnu Ananta Kusuma; Joni Prasetyo (Universitas Trunojoyo Madura, 2013)
DESIGN OF POTENTIAL CELLULASE PRIMER USING MULTIPLE SEQUENCE ALIGNMENT METHOD aBahrul Ulum, bWisnu Ananta Kusuma, c Joni Prasetyo a,bDepartment of Computer Science, Bogor Agricultural University, Bogor, Indonesia aDepartment of Informatics Engineering, Al-Kamal Institute of Science and Technology, Jakarta cRenewable Energy Division, BPPT, Serpong, Indonesia E-mail: aabahrul@gmail.com Abstrak Selulase mempunyai peranan utama dalam pemanfaatan limbah biomassa yang mengandung lignin, hemicellulose, dan cellulose (lignocellulose). Limbah biomassa ini sangat banyak terdapat di lingkungan dan sampai saat ini masih belum dimanfaatkan secara maksimal, dikarenakan banyak mikroorganisme dari alam yang memproduksi enzim selulase dengan jumlah terbatas (aktifitasnya rendah). Dalam rangka meningkatkan produktivitas mikroorganisme untuk menghasilkan selulase, salah satu cara yang dapat diterapkan adalah merancang primer sekuens gen penyandi selulase yang dirangkum dari beberapa mikroorganisme penghasil selulase. Dalam penelitian ini, kami melakukan penyejajaran sekuen DNA penyandi selulase untuk mencari potensial primer untuk meningkatkan produktivitas enzim selulase dengan teknik Multiple Sequence Alignment (MSA). Metode yang digunakan adalah metode progresif (Progressive Alignment Algorithms). Hasil penelitian menunjukan bahwa pada tahap penyejajaran, didapatkan tiga daerah konservatif (conserved regions). Sedangkan pada tahap perancangan dengan beberapa parameter yang telah ditentukan didapatkan 46 pasang primer dari lima sekuen gen penyandi selulase yang didapat dari National Center for Biotechnology Information (NCBI). Kata kunci: Selulase, Multiple Sequence Alignment, Perancangan Primer. Abstract The role of cellulase is very important in degrading cellulose which is abundant in the environment, such as in biomass waste that is containing lignin, hemicellulose, and cellulose. Biomass waste is abundant in the environment and is still not fully utilized, because many of the natural microorganisms that produce cellulase enzymesproduce the enzyme in a limited amount (have low activity). In order to improve the productivity of microorganisms in producing cellulase, one of the ways that can be applied is to design primer sequences of genes encoding cellulase summarized from several cellulase-producing microorganisms. In this research,we perform alignment of DNA sequences coding of cellulase to look for potential primer in order to increase the productivity of cellulase enzymes by Multiple Sequence Alignment (MSA) method. The method used is progressive (Progressive Alignment Algorithms). The results showed that in the alignment phase, three conserved regions were obtained. However, in the planning phase by using some predetermined parameters 46 pairs of primer sequences were obtained from five genes encoding cellulase taken from NCBI. Keywords: Cellulase, Multiple Sequence Alignment, Primer design.